Polymer surfaces and interfaces : acid-base interactions and adhesion in polymer-metal systems /: acid-base interactions and adhesion in polymer-metal systems. (2014) - Starostina, Irina A; Stoyanov, Oleg V; Deberdeev, R. Ya
No abstract available